2017
DOI: 10.1038/jhg.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

The role of READ1 and KIAA0319 genetic variations in developmental dyslexia: testing main and interactive effects

Abstract: Developmental dyslexia (DD) is a complex heritable condition characterized by impaired reading abilities. Two well-replicated candidate risk factors are as follows: (1) regulatory element associated with dyslexia 1 (READ1), which is located in intron 2 of DCDC2 and acts as a binding site for protein regulation of DCDC2 expression; and (2) a three-single-nucleotide polymorphism risk haplotype spanning KIAA0319. Phylogenetically similar READ1 variants showed synergistic effects with the KIAA0319 risk haplotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
4
3
0
Order By: Relevance
“…RU1-1 of READ1 in DCDC2 is significantly associated with impairments in processing speed and attention co-occurring with RD (class 4) in the GRaD sample, even after controlling for the significant effects of age and ADHD diagnosis. The results support prior evidence for a pleiotropic role of DCDC2 in reading and attention performance (Couto et al, 2009;Mascheretti et al, 2017;Riva et al, 2015). To date, there has only been one study that has examined the effects of different READ1 alleles on attention measures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…RU1-1 of READ1 in DCDC2 is significantly associated with impairments in processing speed and attention co-occurring with RD (class 4) in the GRaD sample, even after controlling for the significant effects of age and ADHD diagnosis. The results support prior evidence for a pleiotropic role of DCDC2 in reading and attention performance (Couto et al, 2009;Mascheretti et al, 2017;Riva et al, 2015). To date, there has only been one study that has examined the effects of different READ1 alleles on attention measures.…”
Section: Discussionsupporting
confidence: 88%
“…In Western Europeans, Powers et al (2016) observed a protective effect of RU1-1 when tested for association against severe RD status (Powers et al, 2016). In an Italian sample, Trezzi et al (2017) found no effect of RU1-1 on different reading measures collected in Italian. In the present analysis, the observed effects of RU1-1 were deleterious in Hispanic and African American subjects, though specifically for co-occurring RD with poor processing speed and attention.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…While we have not yet identified the other variants that help confer these differences, identifying these opposing effects of RU1-1 alleles will aid in the discovery of additional factors contributing to these complex traits. The present findings, together with those from Powers et al (2016), and Trezzi et al (2017), highlight that differences in effect of the RU1-1 group of READ1 alleles exist and warrant further investigation to understand why.…”
Section: Discussionsupporting
confidence: 51%
“…In Western Europeans, Powers et al (2016) observed a protective effect of RU1-1 when tested for association against severe RD status (Powers et al, 2016). In an Italian sample, Trezzi et al (2017) found no effect of RU1-1 on different reading measures collected in Italian. In the present analysis, the observed effects of RU1-1 were deleterious in Hispanic and African American subjects, though specifically for co-occurring RD with poor processing speed and attention.…”
Section: Discussionmentioning
confidence: 92%